Hypothetical Subjects in Curriculum Structure for Developing Managerial Competencies in Educational Technology - Kurniawan, Deni; Setiawan, Budi; Perdana, Ryzal; Redzuan, Ikmal (FKIP Universitas Lampung, 2024)
Hypothetical Subjects in Curriculum Structure for Developing Managerial Competencies in Educational Technology. This study aims to understand better one of instructional technology domain: managing. This topic is critical to be learned for better understanding and to have a proper basic theory for developing a curriculum structure of field study, especially to build management competencies. Then, we could propose an alternative for the improvement of the curriculum that has a theoretical foundation. The study used a qualitative approach by applying the Critical Discourse Analysis (CDA) method, a critical analysis of the content of discourse objects that are text, gap, and potential aspect may be, and then proposed an alternative for taking action. Results show; first, there are four subdomains for managing instructional technology, with each orientation and characteristics. Second, Seels and Richey's subdomain of managing instructional technology could guide the study program's curriculum structure development. Third, in case of curriculum of Educational Technology Study Program, Faculty of Education, UPI there are gap between theoretical and document. To overcome the gap in developing instructional technology competencies in managing domain, we propose adding at least one relevant course for the primary and holistic foundation of managing aspect in curriculum structure of Educational Technology Program. Keywords: curriculum, educational technology, critical discourse analysis.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202468